Preparation method of nanocrystalline material, nanocrystalline material, preparation method of shielding sheet, shielding sheet and wireless charging module
By heat-treating the nanocrystalline strip in an atmosphere of inert gas and oxidizing gas to form an oxide film, the problem of high energy loss of the nanocrystalline shielding sheet under the action of an alternating magnetic field is solved, and the effect of reducing the heat generation of the wireless charging module is achieved.
Patent Information
- Application Number
- CN202411853158.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-03-18
AI Technical Summary
The nanocrystal shielding sheets in existing wireless charging modules have high energy loss under the action of alternating magnetic fields, resulting in serious heating of the equipment.
By heat-treating the nanocrystalline strip in an atmosphere of inert gas and oxidizing gas, an oxide film is formed to reduce the generation of eddy current and the diffusion of eddy current, thereby reducing the energy loss of the nanocrystalline material under the action of an alternating magnetic field.
It effectively reduces the hysteresis, eddy current loss and other magnetic losses of nanocrystalline materials under the action of alternating magnetic fields, improves the magnetic properties and square resistance of nanocrystalline materials, and reduces the heat generation of wireless charging modules.
Smart Images

Figure CN119640197A_ABST
Abstract
Description
Technical Field
[0001] The embodiments of the present application relate to the field of wireless charging technology, and in particular to a method for preparing a nanocrystalline material, a nanocrystalline material, a method for preparing a shielding sheet, a shielding sheet, and a wireless charging module. Background Art
[0002] Wireless charging technology, also known as non-contact inductive charging, refers to charging using the principle of electromagnetic wave induction or magnetic resonance. Wireless charging is achieved by setting coils on both sides of the power receiving device and the power supply device using the generated electromagnetic induction or frequency resonance. With the popularization of wireless charging technology, the frequency of wireless charging is increasing, and the disadvantage of severe heating of the device during wireless charging is also gradually emerging.
[0003] At present, the wireless charging module mainly includes a shielding sheet and a charging coil. The materials of the shielding sheet mainly include magnetic bodies such as amorphous and nanocrystalline strips, ferrites, and polymer sheets including magnetic powders; among them, amorphous and nanocrystalline materials are excellent ultra-thin soft magnetic materials, and have high intrinsic magnetic permeability and high saturation magnetic induction, which are suitable for ultra-thin shielding materials. Other materials are difficult to match. In the prior art, the energy loss of nanocrystalline shielding sheet materials under the action of alternating magnetic fields is high, which is not conducive to reducing the heat generation of wireless charging modules. Summary of the invention
[0004] The embodiments of the present application provide a method for preparing a nanocrystalline material, a nanocrystalline material, a method for preparing a shielding sheet, a shielding sheet and a wireless charging module, which can reduce the energy loss of the nanocrystalline shielding sheet under the action of an alternating magnetic field.
[0005] In order to solve the above technical problems, the embodiments of the present application provide the following technical solutions:
[0006] In a first aspect of the present application, a method for preparing a nanocrystalline material comprises: performing heat treatment on a nanocrystalline ribbon using a heat treatment device under an atmosphere of an inert gas and an oxidizing gas, so that the nanocrystalline grains on the surface of the nanocrystalline ribbon undergo an oxidation reaction with the oxidizing gas to form an oxide film on the surface of the nanocrystalline ribbon; and cooling the nanocrystalline ribbon after the heat treatment to obtain a nanocrystalline material.
[0007] In an embodiment of the present application, a nanocrystalline ribbon is heat treated by using a heat treatment device in a mixed gas atmosphere containing an inert gas and an oxidizing gas, so that the nanocrystalline grains on the surface of the nanocrystalline ribbon undergo an oxidation reaction with the oxidizing gas to form an oxide film on the surface of the nanocrystalline ribbon. The oxide film formed on the surface of the nanocrystalline ribbon can effectively reduce the generation of eddy currents flowing on the surface of the nanocrystalline ribbon, hinder the diffusion of eddy currents, thereby reducing the energy loss of the nanocrystalline ribbon under the action of an alternating magnetic field, such as hysteresis loss, eddy current loss and other magnetic losses, and making the prepared nanocrystalline material have good magnetic properties and high square resistance.
[0008] In some embodiments, the oxidizing gas includes oxygen; wherein, in the inert gas and the oxidizing gas atmosphere, the volume fraction of the inert gas is 90 Vol% to 99.9 Vol%, and the volume fraction of the oxygen is 0.1 Vol% to 10 Vol%.
[0009] In some embodiments, the elemental composition of the nanocrystalline ribbon is expressed by the following general formula:
[0010] Fe x Si y Nb z B w Cu v
[0011] Wherein, x, y, z, w and v are used to represent the mass fractions of Fe, Si, Nb, B and Cu in the nanocrystalline strip, respectively, and x=80% to 85%, y=6.0% to 9.0%, z=4.0% to 6.0%, w=1.0% to 2.0% and v=1.0% to 2.0%.
[0012] In some embodiments, before the nanocrystalline ribbon is subjected to segmented continuous heat treatment in an atmosphere of an inert gas and an oxidizing gas to form an oxide film on the surface of the nanocrystalline ribbon, the method further includes: placing the nanocrystalline ribbon in a heat treatment device with an initial temperature not higher than 200°C; evacuating the heat treatment device, and then inputting an inert gas and an oxidizing gas into the heat treatment device.
[0013] In some embodiments, the heat treatment is a segmented continuous heat treatment, and the use of heat treatment equipment to heat treat the nanocrystalline strip includes: step one, raising the heat treatment temperature of the heat treatment equipment to a first temperature range, and keeping it warm in the first temperature range for 10 minutes to 50 minutes, and the first temperature range is 350°C to 450°C; step two, raising the heat treatment temperature from the first temperature range to a second temperature range, and keeping it warm in the second temperature range for 10 minutes to 50 minutes, and the second temperature range is 480°C to 520°C; step three, raising the heat treatment temperature from the second temperature range to a third temperature range, and keeping it warm in the third temperature range for 120 minutes to 180 minutes, and the third temperature range is 540°C to 580°C.
[0014] In some embodiments, the step of cooling the nanocrystalline ribbon after the heat treatment comprises: after step three, cooling the nanocrystalline ribbon in air to room temperature.
[0015] In the second aspect of the present application, a nanocrystalline material is further provided. The nanocrystalline material is prepared according to the method described in the first aspect.
[0016] In a third aspect of the present application, a method for preparing a shielding sheet is provided, the method comprising: preparing a nanocrystalline material according to the method described in the first aspect; and preparing a shielding sheet using the nanocrystalline material.
[0017] In the fourth aspect of the present application, a shielding sheet is also provided, comprising: a plurality of stacked layers of nanocrystalline material, each layer of the nanocrystalline material being bonded by an adhesive; wherein the nanocrystalline material is prepared according to the method described in the first aspect.
[0018] In the fifth aspect of the present application, a wireless charging module is further provided, and the wireless charging module comprises: a wireless charging coil and the shielding sheet described in the fourth aspect, and the wireless charging coil and the shielding sheet are connected.
[0019] It should be understood that the contents described in the summary of the invention are not intended to limit the key or important features of the present disclosure, nor are they intended to limit the scope of the present disclosure. Other features of the present disclosure will become easily understood through the following description. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for use in the embodiments of the present invention. Obviously, the drawings described below are only some embodiments of the present invention, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0021] Figure 1 It is a schematic flow chart of a method for preparing nanocrystalline materials provided in one embodiment of the present application. DETAILED DESCRIPTION
[0022] The principles and spirit of the present disclosure will be described below with reference to several exemplary embodiments shown in the accompanying drawings. It should be understood that the description of these specific embodiments is only to enable those skilled in the art to better understand and implement the present disclosure, and does not limit the scope of the present disclosure in any way. In the following description and claims, unless otherwise defined, all technical and scientific terms used herein have the meanings commonly understood by those of ordinary skill in the art.
[0023] As used herein, the term "including" and similar terms should be understood as open inclusion, i.e., "including but not limited to". The term "based on" should be understood as "based at least in part on". The term "one embodiment" or "the embodiment" should be understood as "at least one embodiment". The terms "first", "second", etc. may refer to different or the same objects, and are only used to distinguish the objects referred to, without implying a specific spatial order, temporal order, order of importance, etc. of the objects referred to.
[0024] For example, Figure 1 A schematic diagram of a process for preparing a nanocrystalline material according to an embodiment of the present invention is shown. Figure 1 The method for preparing the nanocrystalline material comprises the following steps:
[0025] Step 11: heat-treating the nanocrystalline ribbon using a heat treatment device in an atmosphere of inert gas and oxidizing gas, so that the nanocrystalline grains on the surface of the nanocrystalline ribbon undergo an oxidation reaction with the oxidizing gas to form an oxide film on the surface of the nanocrystalline ribbon.
[0026] In an embodiment of the present application, a heat treatment device (e.g., a heat treatment furnace) is used to heat treat the nanocrystalline ribbon in a mixed gas atmosphere including an inert gas and an oxidizing gas. In the process of heat treating the nanocrystalline ribbon, the nanocrystalline grains on the surface of the nanocrystalline ribbon undergo an oxidation reaction with the oxidizing gas, thereby forming an oxide film on the surface of the nanocrystalline ribbon. The oxide film on the surface of the nanocrystalline ribbon can effectively inhibit the eddy current flowing on the surface of the nanocrystalline ribbon, thereby reducing the energy loss of the nanocrystalline ribbon under the action of an alternating magnetic field, such as hysteresis loss, eddy current loss, and other magnetic losses. The oxide film formed on the surface of the nanocrystalline ribbon can hinder the diffusion of eddy currents, so that the nanocrystalline material has good magnetic properties and a higher square resistance.
[0027] In addition, heat treatment of hot nanocrystalline ribbons under inert gas protection can effectively improve the phenomenon of deterioration of nanocrystalline grains during the generation and growth process, and is also conducive to achieving stable control of the heat treatment temperature.
[0028] In an embodiment of the present application, the nanocrystalline ribbon is specifically an iron-based nanocrystalline ribbon, that is, an iron-based nanocrystalline ribbon. The iron-based nanocrystalline ribbon is any suitable iron-based alloy that can be nanocrystallized by heat treatment. In some embodiments, the saturation magnetic induction intensity (Bs) of the nanocrystalline ribbon is 1.2T.
[0029] Specifically, in some embodiments of the present application, the composition of the iron-based nanocrystalline material includes iron (Fe), silicon (Si), boron (B), copper (Cu) and niobium (Nb) elements. In this case, the nanocrystalline ribbon is also referred to as a Fe-Si-B-Cu-Nb alloy. The composition of the iron-based nanocrystalline material can be expressed by the following general formula: Fe x Si y Nb z B w Cu v ; Wherein, x, y, z, w, v are used to represent the mass fractions of the elements Fe, Si, B, Cu and Nb in the nanocrystalline material, respectively. Specifically, in some embodiments, x=80%-85%, y=6.0%-9.0%, z=4.0%-6.0%, w=1.0%-2.0% and v=1.0%-2.0%.
[0030] In other embodiments, the iron-based nanocrystalline material further comprises other trace elements. In this case, the composition of the iron-based nanocrystalline material can be represented by the following general formula: Fe x Si y Nb z B w Cu v M s ; Wherein, M is used to represent trace elements, and s is used to represent the mass fraction of trace elements in the nanocrystalline material. In some embodiments, x=80%-85%, y=6.0%-9.0%, z=4.0%-6.0%, w=1.0%-2.0%, v=1.0%-2.0% and s=1.5%-2.0%.
[0031] In some embodiments, the heat treatment of the nanocrystalline ribbon using the heat treatment equipment may specifically be heat treatment of the nanocrystalline magnetic core formed by winding the nanocrystalline ribbon.
[0032] In some embodiments, the oxidizing gas includes oxygen. The oxidizing gas may be pure oxygen or other suitable oxygen-containing atmospheres such as air. The oxidizing gas is used to react with the nanocrystalline grains on the surface of the nanocrystalline ribbon to generate a dense oxide film on the surface of the nanocrystalline ribbon. In some embodiments of the present application, the oxygen concentration in the oxygen-containing atmosphere is 0.1 Vol% to 10 Vol%.
[0033] In some embodiments, the inert gas is any suitable inert gas, such as nitrogen and / or argon. In some embodiments of the present application, in order to save manufacturing costs, the inert gas may be relatively cheap nitrogen.
[0034] Specifically, in some embodiments, the oxidizing gas atmosphere includes oxygen. In the inert gas and oxidizing gas atmospheres, the volume fraction of the inert gas is 90 Vol% to 99.9 Vol%, and the volume fraction of oxygen is 0.1 Vol% to 10 Vol%.
[0035] In some embodiments, during the heat treatment of the nanocrystalline ribbon, the internal pressure in the heat treatment equipment is 0.01 MPa to 0.02 MPa.
[0036] In some embodiments, the following steps are also included before step 11: placing the nanocrystalline ribbon in a heat treatment device with an initial temperature not higher than 200°C; evacuating the heat treatment device, and then inputting an inert gas and an oxidizing gas into the heat treatment device; for example, nitrogen and oxygen can be input into the heat treatment device in sequence. In this embodiment, when the initial temperature of the heat treatment device is higher than 200°C, placing the nanocrystalline ribbon in the heat treatment device will cause slight grain precipitation in the nanocrystalline ribbon, resulting in reduced performance of the nanocrystalline material. Therefore, in the embodiment of the present application, the initial temperature of the heat treatment device is not higher than 200°C, and the specific size of the initial temperature can be set according to actual conditions, and the embodiment of the present application is not limited thereto.
[0037] In some embodiments, the heat treatment is a segmented continuous heat treatment, that is, the nanocrystalline ribbon is subjected to segmented continuous heat treatment using a heat treatment device. In this embodiment, the generation and growth of nanocrystalline grains in the nanocrystalline ribbon is a continuous process, and the interruption of the heat treatment process will cause the nanocrystalline grains to be non-uniform, resulting in the deterioration of the performance of the nanocrystalline material. Therefore, the embodiment of the present application requires continuous heat treatment of the nanocrystalline ribbon at a specific temperature, that is, a segmented continuous heat treatment process is required to be used to heat treat the nanocrystalline ribbon.
[0038] Step 11 specifically includes the following steps:
[0039] Step 1: The heat treatment temperature of the heat treatment equipment for heat treatment of the nanocrystalline strip is increased from the initial temperature to a first temperature range, and the first temperature range is kept for 10 min to 50 min. The first temperature range is 350° C. to 450° C.
[0040] In this embodiment, after the heat treatment equipment is evacuated and filled with inert gas and oxidizing gas, the heat treatment temperature of the heat treatment equipment is increased from the initial temperature (for example, 200°C) to 350°C to 450°C and maintained for 10 minutes to 50 minutes.
[0041] In some embodiments, the heating rate in step 1 is 10° C. / min-20° C. / min. A relatively high heating rate in step 1 can promote the generation of nanocrystalline grains.
[0042] Step 2: Raise the heat treatment temperature from the first temperature range to the second temperature range, and keep the temperature in the second temperature range for 10 min to 50 min. The second temperature range is 480° C. to 520° C.
[0043] In this embodiment, the heat treatment temperature of the heat treatment equipment is increased from 350° C. to 450° C. to 480° C. to 520° C. and maintained for 10 min to 50 min.
[0044] In some embodiments, the heating rate in step 2 is 2° C. / min-15° C. / min.
[0045] Step 3: Raise the heat treatment temperature from the second temperature range to a third temperature range, and keep the temperature in the third temperature range for 120 min to 180 min. The third temperature range is 540° C. to 580° C.
[0046] In this embodiment, the heat treatment temperature in the heat treatment equipment is increased from 480°C to 520°C to 540°C to 580°C and kept warm for 120min to 180min. The relatively long holding time in step 3 can make the nanocrystalline grains in the prepared nanocrystalline material finer and more uniform in size.
[0047] In some embodiments, the heating rate in step 3 is 2° C. / min-15° C. / min. The appropriate heating rate in steps 1 to 3 is conducive to the formation of nanocrystalline grains, so that the obtained nanocrystalline material has better performance.
[0048] Step 12: Cooling the nanocrystalline ribbon after the heat treatment to obtain a nanocrystalline material.
[0049] In some embodiments, step 12 specifically includes: after step 3, cooling the nanocrystalline ribbon in air to room temperature. For example, the nanocrystalline ribbon can be taken out of the heat treatment device and cooled in air to room temperature.
[0050] Specifically, in some embodiments, in step 12, the cooling rate of the nanocrystalline ribbon in air is 10° C. / min-20° C. / min. A suitable cooling rate can make the prepared nanocrystalline material have better performance.
[0051] In this embodiment, the heat-treated nanocrystalline ribbon is cooled to room temperature in an air environment, which can further form a dense oxide film on the surface of the nanocrystalline grains, thereby further hindering the diffusion of eddy currents on the surface of the nanocrystalline material and further improving the square resistance and magnetic properties of the nanocrystalline material.
[0052] The embodiments of the present application also provide a nanocrystalline material, which is prepared according to the method for preparing the nanocrystalline material provided in the above embodiments.
[0053] The embodiment of the present application also provides a shielding sheet, which includes: a plurality of stacked layers of nanocrystalline materials, each layer of nanocrystalline material is bonded by an adhesive; wherein the nanocrystalline material is prepared according to the preparation method of the nanocrystalline material provided in the above embodiment.
[0054] In some embodiments, the shielding sheet specifically includes a first covering film, a multilayer nanocrystalline material, and a second covering film that are stacked, wherein each layer of the multilayer nanocrystalline material is bonded to each other by an adhesive, which specifically can be acrylic adhesive.
[0055] The embodiments of the present application also provide a method for preparing a shielding sheet, the method comprising: preparing a nanocrystalline material according to the method for preparing a nanocrystalline material provided in the above embodiments, and preparing a shielding sheet using the nanocrystalline material.
[0056] Specifically, in the embodiments of the present application, the method for preparing the shielding sheet using nanocrystalline materials is as follows:
[0057] First: an adhesive is coated on one side of the prepared nanocrystalline material, wherein the adhesive may specifically be an acrylic adhesive; and the thickness of the acrylic adhesive may specifically be 3 μm.
[0058] Secondly: several sheets of nanocrystalline materials coated with adhesive on one side are laminated in multiple layers. Specifically, a layer of adhesive can be coated on the other side of the nanocrystalline material coated with adhesive on one side to obtain a nanocrystalline material coated with adhesive on both sides; several nanocrystalline materials coated with adhesive on both sides are laminated to each other, and then the laminated several nanocrystalline materials coated with adhesive on both sides are laminated with two layers of nanocrystalline materials coated with adhesive on one side, wherein the several nanocrystalline materials coated with adhesive on both sides are located between two nanocrystalline materials coated with adhesive on one side, to obtain a shielding sheet body, at which time, both sides of the shielding sheet body have a layer of acrylic adhesive, and finally the first covering film and the second covering film are respectively affixed on both sides of the shielding sheet body to obtain a shielding sheet.
[0059] In some embodiments, after obtaining the shielding sheet, the shielding sheet may be die-cut according to a predetermined shape and size. The die-cut shielding sheet may be a square with a side length of 50 mm.
[0060] In some embodiments, the die-cut shielding sheet is assembled with the wireless charging coil to obtain a wireless charging module. Specifically, the shielding sheet and the wireless charging coil can be bonded by acrylic adhesive.
[0061] The present application also provides a wireless charging module, which includes: a wireless charging coil and the shielding sheet provided in the above embodiment, wherein the wireless charging coil and the shielding sheet are connected. For example, the shielding sheet and the wireless charging coil can be bonded by acrylic adhesive.
[0062] In some embodiments, the loss of the shielding sheet determines the amount of heat generated by the wireless charging module. The embodiment of the present application helps to reduce the loss of the shielding sheet by increasing the square resistance of the shielding sheet, thereby reducing the heat generated by the wireless charging module.
[0063] The square resistance of the nanocrystalline material prepared by the preparation method of the nanocrystalline material provided in the embodiment of the present application can be as high as 400mohm. The shielding sheet prepared using the nanocrystalline material with high square resistance also has a higher square resistance, so the wireless charging module including the shielding sheet can have lower AC resistance, lower loss and lower heat generation, which is conducive to improving the problem of serious heat generation of the existing wireless charging module during high-frequency use and extending the service life of the wireless charging module. The preparation process of the nanocrystalline material provided in the embodiment of the present application is simple, which is conducive to the mass production of nanocrystalline materials.
[0064] Several embodiments of the present application are provided below.
[0065] Example 1
[0066] Step 1): placing the initial nanocrystalline ribbon in a heat treatment furnace, evacuating the heat treatment furnace, filling it with N2 and O2, and then heat treating the nanocrystalline ribbon, the internal pressure of the heat treatment furnace is 0.01MPa-0.02MPa, wherein the volume fraction of N2 in the heat treatment furnace is 90Vol%-99.9Vol%, and the volume fraction of O2 is 0.1Vol%-10Vol%. The initial temperature of the heat treatment furnace is 200°C.
[0067] Step 2): The heat treatment temperature of the heat treatment furnace is increased from 200°C to 350°C-360°C at a heating rate of 15°C / min, and kept in this temperature range for 10-15min, then the heat treatment temperature is increased to 480°C-485°C at a heating rate of 5°C / min, and kept in this temperature range for 10-15min; then the heat treatment temperature is increased to 540°C-545°C at a heating rate of 5°C / min, and kept in this temperature range for 130-135min.
[0068] Step 3): The nanocrystalline ribbon after the heat treatment in step 2) is taken out from the heat treatment furnace and cooled to room temperature in air, and the cooling rate during the cooling process is 10°C / min-20°C / min.
[0069] Step 4): using acrylic adhesive to laminate several layers of nanocrystalline materials obtained after cooling to obtain a shielding sheet body, and using acrylic adhesive to laminate both sides of the shielding sheet body to the first covering film and the second covering film to obtain a shielding sheet.
[0070] Step 5): Die-cut the shielding sheet obtained in step 4) into a square with a side length of 50 mm to obtain a die-cut shielding sheet, and bond the die-cut shielding sheet to the donut-shaped wireless charging coil by acrylic glue to obtain a wireless charging module.
[0071] Comparative Example 1
[0072] The difference between Comparative Example 1 and Example 1 is that after the heat treatment furnace is evacuated, only N2 is filled in (without O2), and then the nanocrystalline strip is heat treated, and the volume fraction of N2 in the heat treatment furnace is 100 Vol%.
[0073] In the above Example 1 and Comparative Example 1, the model of the nanocrystalline ribbon is 1K107B. The shielding sheets prepared in Example 1 and Comparative Example 1 are named Sample 1 and Sample 2, respectively. After the sample 1 and the sample 2 are magnetized to the same level of real part of magnetic permeability, the square resistance of the surface of the sample 1 and the sample 2 is tested by the four-probe method. The test results of the square resistance of the shielding sheet provided by Example 1 and Comparative Example 1 are shown in Table 1.
[0074] Table 1
[0075] Sample No. Square resistance / mohm Sample 1 400 Sample 2 80
[0076] It can be seen from Table 1 that at the same level of real part of magnetic permeability, the square resistance of sample 1 is significantly higher than that of sample 2; that is, for comparative example 1, the shielding sheet provided by embodiment 1 has a higher surface square resistance, and a higher surface square resistance means a lower conductivity. The embodiment of the present application can reduce the eddy current effect of the prepared nanocrystalline material by introducing oxygen during the heat treatment process, reduce the eddy current loss of the nanocrystalline material, and reduce the heating phenomenon of the shielding sheet.
[0077] Furthermore, in order to verify the influence of the electromagnetic shielding sheet for wireless charging provided in the embodiment of the present application on the wireless charging module, the wireless charging module provided in Example 1 and Comparative Example 1 was subjected to LCR test, and the test results are shown in Table 2, wherein Ls is the inductance; Rs is the AC resistance; Rdc is the resistance value under DC; and Q is the quality factor.
[0078] Table 2
[0079]
[0080] It can be seen from Table 2 that, under the same inductance, the AC resistance of the wireless charging module provided in Example 1 is lower than the AC resistance of the wireless charging module provided in Comparative Example 1. Therefore, the overall electrical performance of the wireless charging module provided in Example 1 is higher than that of Comparative Example 1.
[0081] The wireless charging modules provided in Example 1 and Example 2 were tested for 15W charging efficiency, and the test results are shown in Table 3.
[0082] Table 3
[0083]
[0084] It can be seen from Table 3 that the charging efficiency of the wireless charging module provided in Example 1 is higher than that in Comparative Example 1.
[0085] In summary, the nanocrystalline material prepared by the preparation method of the nanocrystalline material provided in the embodiment of the present application can reduce the Rs of the wireless charging module, providing a basis for reducing the heating problem of electronic products. Compared with the traditional heat treatment process, the heat treatment process of the nanocrystalline ribbon provided in the embodiment of the present application can reduce the imaginary part of the magnetic permeability of the nanocrystalline ribbon and improve the surface square resistance of the nanocrystalline ribbon.
[0086] In the embodiment of the present application, in the steps 1 to 3 of heat treating the nanocrystalline strip, the oxidizing atmosphere in step 1 and step 2 can promote the formation of an oxide film on the surface of the nanocrystalline material, and the oxide film can inhibit the generation of eddy current on the surface of the nanocrystalline material and reduce the eddy current loss of the nanocrystalline material; the relatively high heating rate in step 1 can promote the generation of nanocrystalline grains in the nanocrystalline strip; the relatively long time of heat preservation in step 3 can obtain a nanocrystalline material with fine nanocrystalline grains and uniform nanocrystalline grain size. Placing the heat-treated nanocrystalline strip in an air environment to cool down can further form a dense oxide film on the surface of the nanocrystalline grains, so that the prepared nanocrystalline material has better magnetic properties and higher square resistance as a whole. Therefore, the shielding sheet prepared using the nanocrystalline material also has a higher square resistance, so that the wireless charging module prepared using the shielding sheet can show a lower AC resistance, stronger applicability, less loss, and less heat generation under high-frequency use.
[0087] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit them. Under the concept of the present invention, the technical features in the above embodiments or different embodiments may also be combined, the steps may be implemented in any order, and there are many other changes in different aspects of the present invention as described above, which are not provided in detail for the sake of simplicity. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they may still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a nanocrystalline material, characterized in that: The method comprises: In an atmosphere of inert gas and oxidizing gas, heat-treating the nanocrystalline ribbon using a heat treatment device so that the nanocrystalline grains on the surface of the nanocrystalline ribbon undergo an oxidation reaction with the oxidizing gas to form an oxide film on the surface of the nanocrystalline ribbon; The nanocrystalline ribbon after the heat treatment is cooled to obtain a nanocrystalline material.
2. The method according to claim 1, characterized in that The oxidizing gas includes oxygen; Wherein, in the atmosphere of the inert gas and the oxidizing gas, the volume fraction of the inert gas is 90 Vol% to 99.9 Vol%, and the volume fraction of the oxygen is 0.1 Vol% to 10 Vol%.
3. The method according to claim 1, characterized in that The elemental composition of the nanocrystalline ribbon is expressed by the following general formula: Fe x And y Nb z B w With v Wherein, x, y, z, w and v are used to represent the mass fractions of Fe, Si, Nb, B and Cu in the nanocrystalline strip, respectively, and x=80% to 85%, y=6.0% to 9.0%, z=4.0% to 6.0%, w=1.0% to 2.0% and v=1.0% to 2.0%.
4. The method according to claim 1, characterized in that: Before heat treating the nanocrystalline ribbon under an inert gas and oxidizing gas atmosphere to form an oxide film on the surface of the nanocrystalline ribbon, the method further comprises: placing the nanocrystalline ribbon in a heat treatment device having an initial temperature not higher than 200°C; The heat treatment equipment is subjected to vacuum treatment, and then an inert gas and an oxidizing gas are introduced into the heat treatment equipment.
5. The method according to any one of claims 1 to 4, characterized in that: The heat treatment is a segmented continuous heat treatment, and the heat treatment of the nanocrystalline strip using the heat treatment equipment includes: Step 1: raising the heat treatment temperature of the heat treatment equipment for heat treatment of the nanocrystalline strip from the initial temperature to a first temperature range, and keeping the temperature in the first temperature range for 10 min to 50 min, wherein the first temperature range is 350° C. to 450° C.; Step 2: raising the heat treatment temperature from the first temperature range to a second temperature range, and maintaining the temperature in the second temperature range for 10 min to 50 min, wherein the second temperature range is 480° C. to 520° C.; Step 3: Raise the heat treatment temperature from the second temperature range to a third temperature range, and keep the temperature in the third temperature range for 120 min to 180 min. The third temperature range is 540° C. to 580° C.
6. The method according to claim 5, characterized in that The step of cooling the nanocrystalline ribbon after the heat treatment comprises: After step three, the nanocrystalline ribbon is placed in air to cool to room temperature.
7. A nanocrystalline material, characterized in that: The nanocrystalline material is prepared according to the method according to any one of claims 1-6.
8. A method for preparing a shielding sheet, characterized in that: The method comprises: Prepare nanocrystalline material according to the method according to any one of claims 1 to 6; The nanocrystalline material is used to prepare a shielding sheet.
9. A shielding sheet, characterized in that: The shielding sheet comprises: a plurality of layers of nanocrystalline materials stacked together, each layer of the nanocrystalline materials being bonded together by an adhesive; Wherein, the nanocrystalline material is prepared according to the method according to any one of claims 1-6.
10. A wireless charging module, characterized in that: The wireless charging module comprises: A wireless charging coil and the shielding sheet as claimed in claim 9, wherein the wireless charging coil and the shielding sheet are connected.